Corniculariella brasiliensis, a new species of coelomycetes in the rhizosphere of Caesalpinia echinata (Fabaceae, Caesalpinioideae) in Brazil - Oliveira, Rafael Jose Vilela; Lima, Thaís E.f.; Cunha, Ivone B.; Coimbra, Victor R.m.; Silva, Gladstone A.; Bezerra, José L.; Cavalcanti, Maria A.q. (Phytotaxa, 2014)
Corniculariella brasiliensis sp. nov. is proposed here as a new species of coelomycetes, based on material isolated from the rhizosphere of Caesalpinia echinata. Corniculariella brasiliensis differs from other congeneric species mainly by the shape and size of the conidia. The phylogenetic relationship between Corniculariella and related genera is discussed.